2012
DOI: 10.4018/ijom.2012100102
|View full text |Cite
|
Sign up to set email alerts
|

Second-Order Constructs in Structural Equations

Abstract: Structural equations are extensively used in studies dealing with abstract variables. The authors can choose between first and higher-order constructs but some researchers omit to pursue a rigorous method. Therefore, it is important to know: when is the higher-order construct preferred to the first-order one? In this study, the authors have illustrated this procedure for perceived value and trust. They collected data with students, inviting them to navigate in a website and to fill-in a questionnaire. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The five-factor structure was confirmed. However, a closer investigation of the model indicated that both sensory appeal and playfulness have underlying sub-constructs, and are therefore best designed as second-order constructs ( Khadraoui and Gharbi, 2012 ). The model fit indices Comparative Fit Index (CFI), Tucker-Lewis Index (TLI), Normed Fit Index (NFI), and Root mean square error of approximation (RMSEA) represented a good fit with CFI (0.955), TLI (0.949), NFI (0.921), CMIN/DF (2.232), RMSEA (0.052), and PCLOSE (0.275).…”
Section: Resultsmentioning
confidence: 99%
“…The five-factor structure was confirmed. However, a closer investigation of the model indicated that both sensory appeal and playfulness have underlying sub-constructs, and are therefore best designed as second-order constructs ( Khadraoui and Gharbi, 2012 ). The model fit indices Comparative Fit Index (CFI), Tucker-Lewis Index (TLI), Normed Fit Index (NFI), and Root mean square error of approximation (RMSEA) represented a good fit with CFI (0.955), TLI (0.949), NFI (0.921), CMIN/DF (2.232), RMSEA (0.052), and PCLOSE (0.275).…”
Section: Resultsmentioning
confidence: 99%
“…The five-factor structure was confirmed. However, a closer investigation of the model indicated that both sensory appeal and playfulness have underlying sub-constructs and are therefore best designed as second-order constructs (Khadraoui & Gharbi, 2012). The model fit indices comparative fit index (CFI), Tucker-Lewis index (TLI), normed fit index (NFI), and root mean square error of approximation (RMSEA) represented a good fit with CFI (0.955), TLI (0.949), NFI (0.921), CMIN/DF (2.232), RMSEA (0.052), and PCLOSE (0.275).…”
Section: Dimensions Of Experiential Value In Multi-actor Service Ecos...mentioning
confidence: 99%